Supernova - Meyer, Marissa (Meyer, Marissa. Renegades (Series), 2019)
"All's fair in love and anarchy... Supernova, the epic conclusion to New York Times bestselling author Marissa Meyer's thrilling Renegades Trilogy finds Nova and Adrian struggling to keep their secret identities concealed while the battle rages on between their alter egos, their allies, and their greatest fears come to life. Secrets, lies, and betrayals are revealed as anarchy once again threatens to reclaim Gatlon City."--provided by publisher.